Assessing the anchoring of inflation expectations - Till Strohsal; Lars Winkelmann (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
This paper proposes an ESTAR modeling framework to analyze the anchoring of inflation expectations. Anchoring criteria are empirical estimates of a market implied inflation target as well as the strength of the anchor that holds expectations at the target. Results from daily financial market expectations in the United States, European Monetary Union, United Kingdom and Sweden indicate: First, shorter-term expectations are better anchored than longer-term expectations. Second, expectations are best anchored in the EU, followed by US, Sweden and UK. Third, during the crisis market implied targets mostly decline while the strength of the anchor remains mostly unaffected.
Keywords: E52; E58; C32; 330; monetary policy; anchoring; inflation expectations; break even inflation rates; ESTAR model; Inflationserwartung; Prospect Theory; Bias; Schätzung; USA; Eurozone; Großbritannien; Schweden